2014
DOI: 10.1002/ajmg.a.36597
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept in children with Down syndrome

Abstract: Self-concept is a critical indicator of quality of life but few studies have examined this subject in children with Down syndrome (DS). In this study, we propose a novel methodology to assess the self-concept of children with DS by analyzing their responses towards two dolls, one with a “typically developing” (TD) appearance and one with the phenotypic features of DS. Fifty-four children with DS participated in play sessions with both dolls and were then interviewed to assess doll preference, resemblance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…These between group differences may be attributable to caregiver perception of youth self-perception and self-concept awareness. Youth with DS hold very positive self-perceptions across domains (33), though mental age may affect the ability of an individual with DS’s to form a self-concept (34). Thus, providers may be more likely to persuade caregivers of children with DS about the need to lose weight based on threats to health and effects on physical and social functioning rather than on obesity’s negative effects on self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…These between group differences may be attributable to caregiver perception of youth self-perception and self-concept awareness. Youth with DS hold very positive self-perceptions across domains (33), though mental age may affect the ability of an individual with DS’s to form a self-concept (34). Thus, providers may be more likely to persuade caregivers of children with DS about the need to lose weight based on threats to health and effects on physical and social functioning rather than on obesity’s negative effects on self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected already in toy research: when children with Down's syndrome were given a choice of dolls, they preferred to play with the non-disabled doll as opposed to the doll with features of Down's syndrome (Saha et al, 2014). In addition, the children attributed more positive traits to the non-disabled doll (Saha et al, 2014). Toys, then, are important not just for representation, but for opening dialogue around diversity, impairment, and what this means.…”
Section: Towards Positive Representation In the Toy Industrymentioning
confidence: 92%
“…In fact, diverse dolls might not even be welcomed by the children they represent. Like Clark’s original doll studies, 5 children belonging to marginalized groups have repeatedly been shown to favor typical dolls over those that look like them, 6,8,16 suggesting that they are not immune to recreating societal stigma in the dollhouse. Furthermore, researchers have found that when exposed to Emme dolls representative of a size 16, young girls report greater “desire to be thin when adults” compared to neutral controls, suggesting not only that realistically sized dolls might lack the desired effect on body‐esteem, but that they might instead have the opposite effect of decreasing it 11 .…”
mentioning
confidence: 89%